High‐resolution multiple reaction monitoring method for quantification of steroidal hormones in plasma. (22nd March 2018) - Peti, Ana Paula Ferranti; Locachevic, Gisele Aparecida; Prado, Morgana Kelly Borges; de Moraes, Luiz Alberto Beraldo; Faccioli, Lúcia Helena
Abstract: Multiple reaction monitoring (MRM) is one of the most powerful modes of analysis in liquid chromatographic tandem mass spectrometry for quantification of low‐concentration metabolites in biological samples. The advances in mass spectrometry enabled the development of high‐resolution multiple reaction monitoring (MRM HR ) and became suitable for the more specific analysis of target analytes. This is important for lipidomic studies and contributes in the medical and pharmaceutical fields, primarily in investigating alterations in cells or fluids relevant to various diseases. Therefore, this work proposes the development of the MRM HR method for quantification of circulating steroids. We focused on the determination of corticosterone, 11‐dehydrocorticosterone (11‐DHC), cortisol, cortisone, aldosterone, and progesterone concentration in serum, by using 129 sv male mice exposed to chronic unpredictable stress to validate the quantification. The method was conducted according to the ANVISA normative, adopting a coefficient of variation, as well as relative standard deviation and relative error lower than 15% in linearity, intraday and interday precision, and accuracy. For cortisol, corticosterone, and their inert metabolites (cortisone and 11‐DHC), the lower limit of quantification was 3.9 ng· mL −1, while that for progesterone and aldosterone was 7.8 and 15.6 ng· mL −1, respectively. MRM HR analysis showed that animals submitted to stressors have 4.5 times more corticosterone in their serum than nonstressed mice. However, 11‐DHC concentration does not vary significantly in response to stress for these animals. The results indicate that the method can be applied for quantification of steroids in several biological samples, such as human plasma.